2022
DOI: 10.3389/fimmu.2022.878755
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Agenda - The Involvement of Endoplasmic Reticulum Stress and Unfolded Protein Response in Inflammation-Induced Muscle Wasting

Abstract: Critically ill patients at the intensive care unit (ICU) often develop a generalized weakness, called ICU-acquired weakness (ICUAW). A major contributor to ICUAW is muscle atrophy, a loss of skeletal muscle mass and function. Skeletal muscle assures almost all of the vital functions of our body. It adapts rapidly in response to physiological as well as pathological stress, such as inactivity, immobilization, and inflammation. In response to a reduced workload or inflammation muscle atrophy develops. Recent wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 267 publications
(288 reference statements)
0
5
0
Order By: Relevance
“…Inflammation is considered to be the major predisposing factor for skeletal muscle atrophy, which disturbs the homeostasis of the ER [42,43]. Notably, ER stress also affects the inflammatory process in turn [30]. Therefore, we examined ER stress levels in septic mice and LPS-induced myotubes after NAC treatment and found that ER stress biomarkers followed the same trend as Atrogin-1 and MuRF1, with NAC decreasing their expression levels.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Inflammation is considered to be the major predisposing factor for skeletal muscle atrophy, which disturbs the homeostasis of the ER [42,43]. Notably, ER stress also affects the inflammatory process in turn [30]. Therefore, we examined ER stress levels in septic mice and LPS-induced myotubes after NAC treatment and found that ER stress biomarkers followed the same trend as Atrogin-1 and MuRF1, with NAC decreasing their expression levels.…”
Section: Discussionmentioning
confidence: 95%
“…PERK is activated by auto-phosphorylation as well, leading to a cascade of signals, including the activation of eIF2α and CHOP. The PERK/eIF2α signaling axis also induces the expression of GADD34 [30,31]. Initially, we found that sepsis induces the expression of GRP78, IRE1, sXBP1, eIF2α, GADD34, and CHOP.…”
Section: N-acetylcysteine Inhibits the Activation Of Sepsis-induced E...mentioning
confidence: 92%
“…ICU-AW is associated with multiple risk factors such as sepsis, multiple organ system failure, systemic in ammation, prolonged sedation, prolonged mechanical ventilation, prolonged immobilization, hyperglycemia, glucocorticoids, and neuromuscular blocking agents (17,18) . Critically ill patients with ICU-AW may experience a prolonged decline in quality of life after discharge from the hospital, including di culty swallowing, inability to maintain an upright posture, and physical weakness that lasts for months or even years (19,20) . ICU-AW may result in higher rehab care costs per patient (21) .Consider multiple diagnostic methods for ICU-AW, including muscle biopsy, MRC scale, electromyography, and muscle ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…In severe sepsis, protein breakdown occurs in skeletal muscle, leading to malnutrition in the body, as well as respiratory muscle dysfunction and pulmonary complications. This process is mainly involved in the ubiquitin-proteasome protein degradation pathway ( 22 ). This is consistent with the proteasome up-regulation identified here.…”
Section: Discussionmentioning
confidence: 99%